2021
DOI: 10.3390/nu13051397
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium for Pain Treatment in 2021? State of the Art

Abstract: Background: Magnesium (Mg) is commonly used in clinical practice for acute and chronic pain and has been reported to reduce pain intensity and analgesics consumption in a number of studies. Results are, however, contested. Objectives: This review aims to investigate randomised clinical trials (RCTs) on the effectiveness of Mg treatment on pain and analgesics consumption in situations including post-operative pain, migraine, renal pain, chronic pain, neuropathic pain and fibromyalgia. Results: The literature se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 118 publications
(326 reference statements)
0
16
0
Order By: Relevance
“…Magnesium is a trace metal readily available as an over-the-counter supplement proposed for the treatment of neuropathic pain. It is used in a number of neuropathic pain conditions, including diabetic neuropathy, cancer-related neuropathic pain, chemotherapyrelated neuropathy, and postherpetic neuralgia [54,55].…”
Section: Magnesium For Neuropathic Painmentioning
confidence: 99%
“…Magnesium is a trace metal readily available as an over-the-counter supplement proposed for the treatment of neuropathic pain. It is used in a number of neuropathic pain conditions, including diabetic neuropathy, cancer-related neuropathic pain, chemotherapyrelated neuropathy, and postherpetic neuralgia [54,55].…”
Section: Magnesium For Neuropathic Painmentioning
confidence: 99%
“…Different populations, pathologies, missing information on severity of the patients's disease, different oral Mg chemical forms, or different settings are reported. A recent review [151] observed that eight chemical Mg forms have been studied head-to-head for bioavailability, and concluded that second-generation organic salts (citrate, pidolate, gluconate) are more bioavailable than first-generation inorganic salts (carbonate, chlorure, and oxide). It also stresses that third generation organic salts (bisglycinate, glycerophosphate) are more bioavailable than the other two generations.…”
Section: Prospects Of Mg In the Cardiovascular Disease-sarcopenia-osteoporosis Triadmentioning
confidence: 99%
“…Patients may also have orthopedic surgery after a fracture and experience post-surgical pain, another risk factor for the development of chronic and neuropathic pain [153], with peripheral and central mechanisms of pain at play. The use of Mg in pain relies on the fact that Mg is the physiological blocker of the N-Methyl-D-aspartate (NMDA) receptor, and controls its hyperexcitability in pain chronicization and in learning, cognitive, and emotional processes [151]. The molecular cascades described in pain are also thought to impact sleep, anxiety, and fatigue [151,154].…”
Section: Prospects Of Mg In the Cardiovascular Disease-sarcopenia-osteoporosis Triadmentioning
confidence: 99%
See 2 more Smart Citations